2017
DOI: 10.2147/ott.s131597
|View full text |Cite
|
Sign up to set email alerts
|

Silencing CDR1as inhibits colorectal cancer progression through regulating microRNA-7

Abstract: An increasing number of studies have demonstrated that circular RNAs (circRNAs) can regulate gene expression through interacting with microRNAs. In this study, we analyzed the expression of antisense to CDR1as in colorectal cancer (CRC). CDR1as had a higher expression in CRC tissues compared to adjacent, normal mucosa and was positively associated with tumor size, T stage, lymph node metastasis, and poor overall survival (OS). Downregulation of CDR1as suppressed CRC cell proliferation and invasion and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
154
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 32 publications
(48 reference statements)
3
154
0
1
Order By: Relevance
“…Dysregulated circRNAs may be associated with the diagnosis and therapy of cancers . Several reports have demonstrated that circCDR1as could function as an oncogenic circRNA or tumor suppressor in different cancers because of the change of tumor microenvironment . Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulated circRNAs may be associated with the diagnosis and therapy of cancers . Several reports have demonstrated that circCDR1as could function as an oncogenic circRNA or tumor suppressor in different cancers because of the change of tumor microenvironment . Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging evidence suggests that several circRNAs might contribute to the progression of NSCLC . Accruing evidence demonstrates that circRNA antisense to cerebellar degeneration‐related protein 1 transcript (circCDR1as) could promote the development of hepatocellular carcinoma, colorectal cancer and laryngeal squamous cell carcinoma and inhibit the progression of bladder cancer and ovarian cancer . Importantly, a previous study reveals that circCDR1as acts as an oncogene to facilitate the development of NSCLC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that Cdr1as can sponge miR‐7 and regulate downstream target gene expression (Memczak et al , ). Other studies have shown that Cdr1as plays oncogenic roles in many tumors, such as hepatocellular carcinoma (Yu et al , ) and colorectal cancer (Tang et al , ). In our previous study (Li et al , ), however, we found that Cdr1as sponges miR‐135a instead of miR‐7, restores p21 activity, and mediates cell cycle arrest in bladder cancer cells.…”
Section: Introductionmentioning
confidence: 97%
“…A further layer of regulation is offered by miR-671, which is able to trigger Cdr1as degradation, and as an indirect consequence, to affect miR-7 levels [6]. Knockdown of CDR1as in colorectal cancer and hepatocellular carcinoma cell lines resulted in decreased tumor proliferation, increased miR-7 levels, and downregulation of miR-7 targets [8,9]. It is important to note that all these studies exploited shRNAs and siRNAs to target circRNAs.…”
mentioning
confidence: 99%